Reflect to reflect. - Chew, Lee Fang. (2013)
Karma, the law of cause and effect, is an important feature in Buddhist philosophy. It is the sum of the actions of an individual’s committed in the previous or current state that determines the individual’s future existence. This shows that one has to be aware and mindful of their actions, as it is believed that the taken action will eventually be brought upon oneself. It is inevitable. Thus, this report aims to discuss and explore the law of Karma in the perspective of Buddhist philosophy.